PENGARUH CAMPURAN PAKAN BRAVO 511 TERHADAP PERTUMBUHAN JANGKRIK (Gryllus testaceus) - Delfianizar, Sri Yossa; Lusi Z, S.Si, M.Si, Armein; Kasmeri, S.Si, M.Si., Ria (Pendidikan Biologi, 2014)
ABSTRACTCricket is an insect closely related to grasshoppers, have flat bodies and long antennae.Crickets used as feed for animals such as birds chirped and Arowana fish. Crickets on the market demand is likely to increase while the presence of crickets in the wild has declined. In order pace with demand and rising consumption it, then it tried to cultivate crickets. In crickets maintenance was one of the most important feeding nutritious browing so fast. Crickets growth can be accelerated  by  providing  feed  concentrate  shaped  mashed  first  before  given.  One  of  them bravo511. This study aims to determine the effect of feed mixtures Bravo 511 against crickets weight and feed consumption. Research consumption was implemented in the Tower District of Kuranji Korong Gadang, Padang. This study began in January 2014. This research was CRD (completely randomized design) consisting of 5 treatments and 5 replications. Each treatment was (A) control, (B) K + Brvao 511 0.2 g, (C) K + Bravo 511 0.3 g, (D) K + Bravo 511 0.4 g, and (E) K + Bravo 511 0.5 gr. Data were analyzed by analysis of variance followed by LSD at 5% level. Results showed that administration of a mixed diet of crickets bravo511 significant effect on body weight crickets but has no effect on feed consumption. It can be concluded that the administration of the feed mixture Bravo511 crickets crickets can increase body weight and accelerate the growth of the wing so as to provide rapid time to harvest crickets.